The Effect of Work Stress on Cyberloafing Behavior Mediated by Work-Life Balance in Employees - Aulia Rahmaditha; Rega Riandika; Sandi Nasrudin Wibowo (Indonesian Journal of Business Analytics, 2024)
The purpose of this study was to determine the extent of the effect of work stress on cyberloafing behavior mediated by work-life balance at PT KAI DAOP 3 Cirebon City. This study uses quantitative research with a correlation design that aims to explain the relationship between variables and predict scores. The sample in this study amounted to 66 respondents and data was obtained through questionnaires. The results of a simple linear regression analysis showed that there was a significant influence between the work stress variable (X) and the work-life balance variable (Z) of 19.5%. While the results of multiple linear regression analysis showed that there was no significant influence between the work stress variable (X) on the cyberloafing variable (Y) and there was a significant influence between the work stress variable (X) and the work-life balance variable (Z) on the cyberloafing variable (Y) by 18.7%. The conclusion and implication of the study as a whole is that it highlights the importance of work-life balance in coping with work stress and cyberloafing. The results also suggest that work-life balance mediates cyberloafing behavior and may be an influential factor in most employees and a small percentage unaffected by work-life balance and other factors outside of the study.